Cosmic accelerated expansion of the Universe with phantom fluid - Keskin, Ali İhsan (CANADIAN JOURNAL OF PHYSICS, 2019)
The phantom behavior of the Universe is discussed in an extended version of Gauss-Bonnet gravity. Following the method proposed by the author (Int. J. Mod. Phys. D, 27, 1850078. 2018. doi:10.1142/S0218271818500785), we obtain a viable cosmological model for the phantom phase of the Universe. We find a condition for m in the model similar to G(m), which shows phantom expansion of the Universe. On the other hand, using a phantom source term similar to T-2n in the model we observe that the term similar to G(n), with n > 3/4, gives a phantomic space-time expansion. This form (G(n) + T-2n) obtained for the phantom phase of the Universe exhibits a similar form to Einstein's gravity theory (R + L-m). However, we addressed the cosmic coincidence problem for the model.
Keywords: Phantom expansion; f(G, T) gravity; Scalar fields; Power law solutions; Cosmic acceleration